Perfil epidemiológico de recém-nascidos com retinopatia da prematuridade do Hospital Universitário da Universidade Federal do Maranhão - Rebeca Costa Castelo Branco; Valéria de Jesus Menezes de Menezes; José Francisco Das Chagas Avelar; Marynea Silva do Vale; Patrícia Franco Marques (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To describe the profile of premature newborns and exploratory analysis of factors associated with the development of retinopathy of prematurity (ROP) at the University Hospital of the Federal University of Maranhão (HU-UFMA). METHODS: This is a cross-sectional study based on data from the medical records of premature newborns treated at the University Hospital of the Federal University of Maranhão (HU-UFMA), from 2015 to 2020. Possible statically significant associations for the development of ROP were evaluated: sex, gestational age, birth weight, length, head circumference, length of hospital stay, APGAR and others. The significance level adopted was 5% (p<0.05). RESULTS: It was found that, in children with a confirmed diagnosis of ROP, the most prevalent sex was female (50.95%), the mean gestational age was 29.08 weeks, the most frequent outcome was hospital discharge (70, 71%), mean birth weight was 1,089 grams, mean hospital stay was 45.44 days, mean length was 35.73 cm, mean head circumference was 26.06, Apgar most prevalent in the first minute was in the range from 4 to 7 (43.32%) and in the fifth minute from 8 to 10 (56.40%). CONCLUSIONS: The prevalence of ROP cases was 61.40% among newborns followed up at a reference service in the state of Maranhão. It was observed that the lower the gestational age and birth weight, the greater the risk of developing ROP.